Pengaruh Macam dan Perbandingan Volume Pupuk Kandang terhadap Pertumbuhan LCC Mucuna bracteata pada Tanah Latosol - Wati, Kurnia Eka; Andayani, Neny; Parwati, Wiwin Dyah Ully (Program Studi Agroteknologi INSTIPER, 2024)
Legume Cover Crop (LCC) used in Palm plantations has not yet produced for weed control because there are still large open lands. To prepare LCC seedling of the Mucuna bracteata species, a medium is required that provides good root growth, inter alia, with the addition of organic material derived from various animal debris. This research aims to find out the influence as well as the interaction of type and comparison of the volume of cage fertilizer on the growth of LCC Mucuna bracteata on the latosol soil that has been carried out at the KP2 INSTIPER, Maguwoharjo, Yogyakarta, Yogyakarta and at the Central Laboratory, Instiper on April 20, 2021 to June 30, 2021. This research uses a complete random design (RAL) or Completely Randomized Design (CRD) method that consists of two factors. The first factor is a type of cage fertilizer that consists of three levels, namely cage, chicken and goat fertilizers. The second factor is the comparison of the volume of the soil of the latosol with the cage of 3 levels of 1:1, 2:1, and 1:2 with 10 repetitions. The results of the study were analysed with the analysis of variance prints at the significance level of 5%. The effective treatment was further tested with the Duncan Multiple Range Test (DMRT) using the significance level of 5%. Results of the analysis showed that the treatment of cage fertilizer and the comparison of the soil volume of latosol with cage fertilizer did not have a real interaction and both treatments gave the same effect on the growth parameters of plants, including its length, leaf number, shoots number, top fresh weight, top dry weight, root length, fresh root weight and dry roots of Mucuna brate plant. Cage fertilizer and volume comparison gives the same bet on all the growth parameters of Mucuna bracteata.